Diverse Profiles of Biofilm and Adhesion Genes in Staphylococcus Aureus Food Strains Isolated from Sushi and Sashimi - Puah, Suat Moi; Tan, Jin Ai Mary Anne; Chew, Ching Hoong; Chua, Kek Heng (Wiley, 2018)
Abstract: Staphylococcus aureus is able to form multilayer biofilms embedded within a glycocalyx or slime layer. Biofilm formation poses food contamination risks and can subsequently increase the risk of food poisoning. Identification of food-related S. aureus strains will provide additional data on staphylococcal food poisoning involved in biofilm formation. A total of 52 S. aureus strains isolated from sushi and sashimi was investigated to study their ability for biofilm formation using crystal violet staining. The presence of accessory gene regulator (agr) groups and 15 adhesion genes was screened and their associations in biofilm formation were studied. All 52 S. aureus strains showed biofilm production on the tested hydrophobic surface with 44% (23/52) strains classified as strong, 33% (17/52) as moderate, and 23% (12/52) as weak biofilm producers. The frequency of agr-positive strains was 71% (agr group 1 = 21 strains; agr group 2 = 2 strains; agr group 3 = 12 strains; agr group 4 = 2 strains) whereas agr-negative strains were 29% (15/52). Twelve adhesion genes were detected and 98% of the S. aureus strains carried at least one adhesion gene. The ebps was significantly (p <.05) associated with strong biofilm producing strains. In addition, eno, clfA, icaAD, sasG, fnbB, cna, and sasC were significantly higher in the agr-positive group compared to the agr-negative group. The results of this study suggest that the presence of ebps, eno, clfA, icaAD, sasG, fnbB, cna, and sasC may play an important role in enhancing the stage of biofilm-related infections and warrants further investigation. Practical Application: This work contributes to the knowledge on the biofilm formation and the distribution of agr groups in S. aureus strains as well as microbial surface components in recognizing adherence matrix molecules of organisms isolated from ready-to-eat sushi and sashimi. The findings provide valuable information to further study the roles of specific genes in causing biofilm-related infections.